EVALUTION AND CALIBRATION OF MINIATURE CIRCUIT BREAKER - Singh, Ramandeep; Singh, Baljinder (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The purpose of this paper is to examine the significant developments in MV and LV switchgear technology over the last few decades and why they are only recently beginning to benefit the users. A recent development now has sufficient field experience to show how through innovative design it has been possible to vastly improve an auto-reclosing circuit breaker. The author believes that the same innovative ideas will soon be applied to all types of switchgear. Â The next generation of military switchgear is likely to be developed for the Electric Warship. Irrespective of which distribution supply is used the next generation of switchgear should benefit from the new technology. Calibration of Miniature Circuit Breaker takes a lot of time. Calibration is done to satisfy the International Standards so that all the MCBs are standardized. In this paper we concerned with decreasing this calibration time of MCBs whose rated current is less than or equal to 32 Amps. Calibration can be done by two methods, wiz, and Dual current and single current parameter method. This paper also deals with the decrease in the Calibration time and increase in Production efficiency by the use of later method which is a modification of the former one proposed and implemented here. This is done by employing faster motor for the calibration. Â A recent development now has sufficient field experience to show how through innovative design it has been possible to vastly improve an auto-reclosing circuit breaker. The author believes that the same innovative ideas will soon be applied to all types of switchgear.